The fall of national identity in Chinua Achebe's Things Fall Apart - Abu Jweid, Abdalhadi Nimer Abdalqader (Universiti Putra Malaysia Press, 2016)
This article examines Chinua Achebe's Things Fall Apart within a postcolonial discourse. While the majority of postcolonial critiques argue over indigenous identity, this study explores the deterioration of national identity in Things Fall Apart. Such deterioration is brought about by the spiritual and tentative defeat inherent in the failure of the protagonist, Okonkwo, to face the colonial whites. Ultimately, the protagonist's failure leads to a tragic death. In the novel's context, Achebe exhorts the fall of national identity and its pathetic aftermath. The deterioration in national identity symbolically correlates to the protagonist's personal irresolute experience which is at first physically powerful but in the end spiritually weak. The focus of this article is a textual analysis of Achebe's Things Fall Apart, applying postcolonial theoretical concepts, especially aboriginality, hegemony, subaltern and identity. These concepts facilitate a smouldering conceptualisation of national identity as it is exterminated in the novel. Thus, the these terms will be cited mainly with reference to Bill Ashcroft, Gayatri Spivak, and Laura Chrisman's postcolonial critiques.